Validity and Practicality Test of e-Student Worksheets Using the ARCS (Attention, Relevance, Confidence, and Satisfaction) Model on Acid-Base Concepts - Nindya Cika Ferdian; Lenny Anwar; Herdini Herdini (International Journal of STEM Education for Sustainability, 2025)
Electronic Student Worksheets (e-Student Worksheets) include teaching materials that are intensively developed to facilitate their learning process. One website with many features that can be utilized to create E-Worksheet is Liveworksheets. This study aims to develop an E-Worksheet based on the Attention, Relevance, Confidence, and Satisfaction (ARCS) model on the subject of acid-base that is valid and knows the user response. The research method used is Research and Development (RD) with the 4-D development model. Research instruments in the form of validation sheets were given to 3 validators, and user response sheets were given to 2 chemistry teachers, 10 students from a Senior High School A in Pekanbaru, and 10 students from a Senior High School B in Pekanbaru, Indonesia. Material expert E-Worksheet validation obtained a total average score of 97.3% with valid criteria and media expert validation obtained a total average score of 100% with valid criteria. User response obtained results with an average score of 95.3% from teachers and students of 89% with very good criteria. From the research results, it can be concluded that the ARCS-based E-Worksheet using Liveworksheets on acid-base material can be used as teaching materials in the learning process.